An investigation into the diffusion of the cryptocurrency innovation - Wesley, Matthew (2018)
The information age has dawned upon us through the comprehensive and boundless adoption of the internet; E-banking and smart-phones thus, causing a reliance on online transaction sys-tems reducing the need to handle tangible cash notes. The current monetary system is arguably on the cusp of an evolutionary moment through the adoption of virtualised currencies, this phe-nomenon potentially possesses the next metamorphic step in contemporary global economic money.